Requirement of soft skills among graduating accounting students : employers and UiTM students’ view / Salwa Muda, Anita Che Hassan and Ros Norita Abdul Samad - Muda, Salwa; Che Hassan, Anita; Abdul Samad, Ros Norita (2009)
The dramatic changes in the workforce lead employers to hire candidates who are academically and technically proficient. Accounting graduates must equip themselves with numbers of characteristics as required by their potential employers. However, there are differences in views between employers and graduating accounting students regarding the characteristics that must be possess by the new employees. Thus, the present study seeks to identify the characteristics that accounting graduates of UiTM perceived to be important, and to recognize the requirement of characteristics needed by employers (Public Accounting Firms). The result shows that students are in agreement with employers’ opinion regarding the importance of work quality, work attitude, and punctuality. There is a significant difference on the importance of technical skills that comprises of working knowledge of computers, and the ability to assimilate new technologies. In addition, the graduating accounting students overvalue the importance of creative thinking, delegation, oral communication skills, written communication skills, work attendance, work quantity, research skills, and project management, as compared to the employers who overvalue the importance of dependability, looking for ways to improve job performance, acceptance of constructive criticism.